Using Failure Modes to Enhance What‐If Analysis. Issue 3 (15th November 2013) - Collins, Robert L.
<x xml:space="preserve">Abstract</x> What‐If Analysis is one of the most commonly used methods for performing a process hazards analysis (PHA) of a potentially hazardous chemical process. It is used so widely because it is perhaps the simplest and quickest way to perform a PHA. The speed of the PHA method often sacrifices quality by missing important scenarios simply because the right what‐if question was never asked. This article will show how the quality of a What‐If Analysis can be enhanced using failure modes for system component types without significantly increasing study time. A "smart" system using off‐the‐shelf computer software combined with specially designed subroutines or macros is used to demonstrate this process. © 2013 American Institute of Chemical Engineers Process Saf Prog 33: 231–236, 2014